Penerapan Green Purchasing dalam Mendukung Lingkungan Keberlanjutan pada Hotel Bintang 5 - Sasha Reva Pramesti; Cokorda Gede Putra Yudistira; Rifqi Nurfakhrurozi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study examines the implementation of environmentally responsible procurement in supporting environmental sustainability at a 5-Star Hotel, focusing on supplier selection that meets environmentally friendly criteria and on procurement processes oriented toward reducing, reusing, and recycling materials. This study uses a descriptive qualitative method with Miles and Huberman's interactive analysis model. Data were obtained through observation, interviews, and documentation with the procurement manager, procurement staff, and Head of Receiving. The results show that environmentally responsible procurement has been implemented based on the responsible sourcing guidelines of the international hotel network, but has not yet fully met all supplier selection criteria and has not fully eliminated single-use packaging, so its impact on environmental sustainability has not been significant. This finding confirms the importance of consistent implementation of environmental policy at the operational level.